Estimation of Carbon Stored Mangrove Vegetation in Small Islands Bunaken National Park - Schaduw, Joshian Nicolas William (Jurnal Ilmiah Platax, 2021)
Mangrove ecosystems have many roles in maintaining balance in coastal areas and on small islands because they are very productive and contribute as a source of organic carbon and other nutrients, and can absorb carbon in the atmosphere and store it in biomass and sediments so that mangroves play a very important role in mitigating global climate change. The purpose of this study is to find out how much potential carbon stock is stored in mangrove vegetation in Bunaken National Park North Minahasa Region (Mantehage Island and Nain Island). This study uses the line transect method for sampling plots in data collection, where at each research station 3 plots measuring 10x10 m2 are made with a distance that adjusts to the condition of the mangroves. Each individual in the plot was recorded for the type, number, and circumference of the tree trunk. Calculation of the biomass of mangrove trees using the allometric equation Komiyama et al., (2005) and estimating the amount of carbon (C) stored using the Brown (1997) and IPCC (2006) equations. The results of the estimation of the total carbon stored in mangrove vegetation in KDP National Park Bunaken North Minahasa Region (Mantehage Island and Nain Island) the total potential of biomass and carbon stored in mangrove vegetation in KDP TNB North Minahasa Region (Mantehage Island and Nain Island) amounted to 75.91 tons /ha or the equivalent of 35.68 tons C/ha.Keywords: Small islands; Mangrove; Biomass; CarbonAbstrakEkosistem mangrove memiliki banyak peranan dalam menjaga keseimbangan di wilayah pesisir maupun pada pulau-pulau kecil karena sangat produktif dan berkontribusi sebagai sumber karbon organik dan nutrien lainnya, serta dapat menyerap karbon di atmosfer dan menyimpannya dalam biomassa dan sedimen, sehingga mangrove sangat berperan dalam mitigasi perubahan iklim global. Tujuan penelitian ini yaitu mengetahui seberapa besar potensi stok karbon tersimpan pada vegetasi mangrove di PPK Wilayah Minahasa Utara (Pulau Mantehage dan Pulau Nain). Penelitian ini menggunakan metode garis transek petak contoh dalam pengambilan data, dimana pada setiap stasiun penelitian dibuat 3 plot berukuran 10x10 m2 dengan jarak menyesuaikan keadaan mangrove. Setiap individu yang terdapat dalam plot dicatat jenis, jumlah, dan keliling lingkar batang pohon. Perhitungan biomassa tegakan pohon mangrove menggunakan persamaan allometrik Komiyama et al., (2005) dan mengestimasi jumlah karbon (C) tersimpan menggunakan persamaan Brown (1997) dan IPCC (2006). Hasil estimasi total karbon tersimpan pada vegetasi mangrove di PPK Taman Nasional Bunaken Wilayah Minahasa Utara (Pulau Mantehage dan Pulau Nain) total potensi biomassa dan karbon tersimpan vegetasi mangrove di PPK TNB Wilayah Minahasa Utara (Pulau Mantehage dan Pulau Nain) yakni sebesar 75,91 ton/ha atau setara 35,68 ton C/ha.Kata Kunci: Pulau-Pulau Kecil (PPK); Mangrove; Biomassa; Karbon